REPRESENTATION OF THE STATE’S INTERESTS IN COURT BY THE PROSECUTOR: IN SEARCH OF TRENDS IN THE DEVELOPMENT OF THE CONCEPTUAL FRAMEWORK - Maryna Stefanchuk (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право»)
Introduction. The article analyzes the trends in the development of the conceptual substantiation of the prosecutor’s representation of the State’s interests in court as one of the functions of the Public Prosecutor’s Office in Ukraine, which is one of the constitutionally enshrined areas of the prosecutor’s office’s activities aimed at protecting the interests of the State in court in exceptional cases and in accordance with the procedure established by law. The legal uncertainty inherent in the legal regulation of this function of the Public Prosecutor’s Office leads to an active scientific and expert-practical discourse, which is periodically updated with the emergence of new legal positions of courts or legislative initiatives in this area, which creates preconditions for identifying new trends in the development of the conceptual justification of this function of the Public Prosecutor’s Office. The purpose of the article is to highlight the current trends in the development of the conceptual substantiation of the representative function of the Public Prosecutor’s Office through the prism of dynamic changes in legislation, ambiguity of its application practice and legislative initiatives in the field of the issues under study.